Gender Analysis of Family Traditions, Parent-Child Ties, and Happiness in Generation Z during Covid-19 Pandemic: Gender Analysis of Family Traditions, Parent-Child Ties, and Happiness in Generation Z during Covid-19 Pandemic - Avia Maulidina; Herien Puspitawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
Generation Z has faced various transformations in life due to the Covid-19 pandemic. This study analyzes family traditions, parent-child ties, and happiness in Generation Z during the Covid-19 pandemic based on gender. This study used a quantitative approach with a non-probability voluntary sampling method involving 42 men and 130 women of generation Z who are college students and domiciled in the Special Region of Yogyakarta. Data were analyzed using descriptive analysis, independent t-test, and PLS-SEM. The results showed that family traditions varied in the category; meanwhile, parent child-ties and happiness were moderate. There were no significant gender differences in family traditions and parent-child ties, but women reported significantly lower happiness than men during the pandemic. This is in line with the results of the PLS-SEM model, which showed that gender had a negative effect on the happiness of generation Z. PLS-SEM model showed that family traditions and parent-child ties had significant positive effects on happiness. These findings imply that in the middle of Covid-19 pandemic social restrictions, families must strengthen family traditions and optimize parent-child ties so that the happiness of generation Z can be maintained, both for men and women.